Arf6 and its ZEB1-EPB41L5 mesenchymal axis are required for both mesenchymal- and amoeboid-type invasion of cancer cells. (3rd September 2018) - Handa, Haruka; Hashimoto, Ari; Hashimoto, Shigeru; Sabe, Hisataka
ABSTRACT: Modes of cancer invasion interchange between the mesenchymal type and amoeboid type in response to the microenvironment, in which RhoA and Rac1 are selectively required to perform different modes of actin-cytoskeletal remodeling. Membrane remodeling is another integral part of invasion. Arf6 regulates the recycling of molecules at the cell periphery, and is often overexpressed in malignant cancers together with its effector AMAP1/ASAP1/DDEF1. This pathway promotes mesenchymal-type invasion when AMAP1 binds to EPB41L5, a mesenchymal-specific protein induced by ZEB1. Here we show that the Arf6-AMAP1-EPB41L5 pathway, and ZEB1, are also crucial for amoeboid-type invasion, via receptor tyrosine kinase and G-protein-coupled receptor signaling. Thus, Arf6 appears to be necessary for both RhoA- and Rac1-driven cancer invasion. Moreover, amoeboid-type cancer invasion may require the activation of some type of mesenchymal program within the cancer cells.